Copidosoma floridanum (Hymenoptera: Encyrtidae) Rapidly Alters Production of Soldier Embryos in Response to Competition. (18th July 2017) - Smith, Margaret S.; Shirley, Andrew; Strand, Michael R.
Abstract: Most social insects are free living and produce castes that develop in response to extrinsic environmental cues. Caste-forming polyembryonic insects, in contrast, are all endoparasitoids that form social groups inside the bodies of host insects. The best studied polyembryonic wasp is Copidosoma floridanum (Ashmead), which produces ∼3, 000 clonal offspring that develop into two castes named reproductive and soldier larvae. Caste determination in this species is mediated by whether or not embryos inherit primary germ cells (PGCs). Prior results showed that C. floridanum increases the proportion of female soldier larvae it produces per host in response to other parasitoids like Microplitis demolitor . Here we show that caste ratio shifts occur through increased formation of embryos lacking PGCs. Our results further indicated that increased soldier production was a specific response to multiparasitism elicited by the chorion of M. demolitor eggs.